Entropia de cadeias lineares polidispersas - Adão Neto, Minos Martins (2009)
We consider the entropy of linear polydisperse chains placed (adsorbed) on a lattice. These chains are formed by monomers with an excluded volume interaction. In particular, we study a model for equilibrium of polymerization, where the polydispersivity is determined by two activities, for internal and endpoint monomers of a chain. We solve the problem using transfer matrix techniques in one-dimensional lattices and on hierarchical lattice Bethe and Husimi lattices with arbitrary coordination number, obtaining an expression for the entropy as a function of the density of monomers and mean molecular weight of the chains. We compare this entropy with the one for the monodisperse case and we obtain the distribution of molecular weights.